선진국 농업부문 바이오매스 이용활성화 정책과 시사 : “농업분야 바이오매스의 이용활성화를 위한 정책방향과 전략” 자료집(Ⅰ) - 강창용 (한국농촌경제연구원, 2006)
This is the first year report of a two-year research project on 'Policy Directions and Strategies for Boosting Biomass Utilization in the Agricultural Sector' to be completed in 2007. This study aims to establish mid- and long-term policies and strategies regarding the activation of biomass in agriculture. The objective of the first year report is to grasp the actual state and policies of biomass utilization in advanced countries such as Japan, Germany, and the U.K. and to make policy suggestions in order to accelerate biomass utilization in Korea. The contents of the report can be summarized as follows: First, the use of biomass will be ever more highlighted in view of the securement of energy resources, the prevention of global warming, the construction of a recycling based society, and the creation of incomes and job opportunities. Second, advanced countries concentrate on providing government support to develop and spread the use of alternative energy sources, thereby leaving something to be desired by Korea to follow suit. In this sense, a comprehensive system is urgently needed to revitalize biomass use. Also, categorical and step-by-step strategies are essential to promote the use of biomass. Researchers: Kang Chang-Yong, Park Hyun-Tae, Shin Yong-Kwang, Min Kyung-Taek E-mail address: cykang@krei.re.kr